The effect of Pressurised Intraperitoneal Aerosol Chemotherapy on the quality of life of patients with primary diagnosed ovarian cancer with peritoneal carcinomatosis during combined treatment - A. S. Dzasokhov; A. A. Kostin; V. L. Astashov; A. V. Turiev; A. D. Uskov (Исследования и практика в медицине, 2023)
Purpose of the study. To evaluate the effect of Pressurized IntraPeritoneal Aerosol Chemotherapy (PIPAC) on the quality of life of patients during standard combined treatment of newly diagnosed ovarian cancer.Patients and methods. A combination of surgical cytoreduction with a simultaneous session of intra‑abdominal aerosol chemotherapy under pressure and subsequent systemic chemotherapy within the framework of a single hospitalization was used. The study included 164 patients (79 in the main group, 85 in the control group). All patients were operated on at the first stage, all underwent systemic cytostatic therapy according to the TS scheme (6 courses with an interval of 21 days). In the main group, 3 PIPEC sessions were added to standard treatment: the first one simultaneously with cytoreductive surgery, followed by 2 more PIPAC sessions with an interval of 42 days. To assess the quality of life, the EORTC‑QLQ – C30 questionnaire was used, which the patients filled out 4 times: before the cytoreductive stage, and then after completing the first, third and fifth courses of systemic polychemotherapy (PCT).Results. Before the start of treatment in the control group, the average general condition was 1.6 ± 1.1 points, then 1.32 ± 1.0 points, then 0.96 ± 0.97 and 0.78 ± 0.87 points at the end of the 6th course of systemic PCT. A similar situation has developed in the main group. The average baseline value before treatment was 1.7 ± 1.1 points, with the second questionnaire – 1.3 ± 1.1 points, with the third questionnaire – 0.66 ± 0.83, and 0.43 ± 0.75 points with the fourth questionnaire. In the control group, the average assessment of the quality of life before treatment was 55.0 ± 11.0 points, and then sequentially with the following three surveys 50,8 ± 7,5, 47 ± 8, 45,6 ± 8,1 points, which indicates an improvement in the quality of life against the background of ongoing treatment. In the main group, the basic level of assessment of the quality of life was 53.8 ± 11.3 points. Subsequently, an improvement in the indicators was also revealed: 49.6 ± 7.5 points, 44.2 ± 5.3 points and 42.1 ± 5.4 points, respectively. The homogeneity of the distribution in the groups was established by means of an accurate two–way Wilcoxon–Mann‑Whitney rank sum criterion, the actual significance level was p = 0.498. A two‑factor model of nonparametric analysis of variance (ANOVA) was used to analyze the data obtained. To identify a significant difference between the indicators at different stages of the study, the Page rank criterion for an ordered alternative and an algorithm based on the Friedman rank sum test were used. As a result, it was shown that the revealed positive dynamics of indicators within the groups over the entire study period is statistically significant (p < 0.0001).Conclusion. The results of the study showed that PIPAC not only does not reduce the quality of life and does not worsen the well‑being of patients, but also improves these indicators by the time of completion of combined treatment (after the 6th course of systemic PCT): in the main group, the overall ECOG condition at this stage was estimated at 0.43 ± 0.75 points, in the control group – 0.78 ± 0.87 points. The survey of patients using EORTC‑QLQ – C30 at this stage showed that in the main group the indicator was 42.1 ± 5.4 points versus 45.6 ± 8.1 points in the control group of the study.